Morphological applied study For the breaks of Surat Al-Kahf (Journal of the College of Basic Education, 2022)
Research SummaryThe Holy Qur’an is the miraculous word of God whose wonders do not perish or expire.The importance of research is highlighted in the following:1- Highlighting the issue of the Quranic comma in Surat Al-Kahf, and highlighting the morphological study of these commas.2- Serving the Book of God, as it is a book of guidance and guidance, and it is miraculous in its words, sentences, and chapters.3- A statement that this subject has not been researched in an independent written manner before.4- The importance of this study stems from the importance of its topic, as it deals with a topic on which scientists have not written a scientific treatise before.5- The desire to highlight the impact of the Noble Qur’an in the morphological lesson, represented by the commas of its verses.